Randomized Trial of Pegmolesatide for the Treatment of Anemia in Patients With Nondialysis CKD - Jianteng Xie; Aicheng Yang; Hongyu Qiu; Xiaomei Peng; Wanhong Lu; Xiangyang Huang; Qinkai Chen; Aimin Zhong; Shuifu Tang; Qin Wang; Chuan Li; Liangliang He; et al. (Kidney International Reports)
Introduction: Pegmolesatide has been recently approved for treating anemia in chronic kidney disease (CKD) patients in China. We presented the results of the pivotal study conducted in patients with nondialysis-dependent (NDD)-CKD with anemia. Methods: This randomized, active-controlled, open-label, noninferiority phase 3 study was conducted across 38 centers in China. Eligible patients were randomly assigned to receive subcutaneous injection of pegmolesatide in the upper arm once every 4 weeks or epoetin alfa weekly or biweekly, with doses adjusted to maintain hemoglobin (Hb) level of 100 to 120 g/l. The primary outcome was the mean change in Hb level from the baseline during the efficacy evaluation period. Noninferiority of pegmolesatide to epoetin alfa was established if the lower limit of the 2-sided 95% confidence interval (CI) was ≥ −10 g/l. Results: A total of 173 patients received at least 1 dose of pegmolesatide (115 patients) or epoetin alfa (58 patients). During the efficacy evaluation period, the mean change in Hb from baseline level was 19.2 g/l in the pegmolesatide group and 15.4 g/l in the epoetin alfa group with a between-group difference of 3.8 g/l (95% CI: 0.7–6.9). The incidence of adverse events (AEs) and serious AEs (SAEs) were similar between groups, with hypertension being the most reported AE related to the study drug. No drug-related hypersensitivity reactions or fatal events were observed. Conclusion: Pegmolesatide demonstrated comparable efficacy to epoetin alfa in elevating and maintaining Hb levels in patients with NDD-CKD with anemia without new safety concerns (ClinicalTrials.gov identifier: NCT03903809).